The Difference of a Child (Walad) Concept in Islamic Inheritance Law and its Implications on The Decisions of the Religious Courts in Indonesia - Furqan, Ana Amalia; Alfitri, Alfitri; Haries, Akhmad (Mazahib, 2018)
This article is based on the fact that there is still the disparity of decisions among the Religious Court Judges on heirs, especially a child (walad), when handling the inheritance disputes. This is because there is a general provision of the meaning of walad contained in the Indonesian Compilation of Islamic Law (KHI) in which it includes both a son and a daughter. In addition, there is no obligation for Religious Court Judges to use the KHI as the basis for legal considerations, allowing for some Religious Court Judges to use the classical Islamic Jurisprudence (fiqh) as the legal basis in deciding a case. This article aims to investigate the impact of the general concept of walad (a child) and measures should be taken the Government to accommodate the legal reference material for Religious Court Judges, especially the KHI and the classical Islamic Jurisprudence (fiqh). It employs normative legal research which primarily examines the decisions of the Religious Courts in East Kalimantan, specifically Samarinda, Tenggarong and Tanah Grogot. The findings reveal that since there is no obligation for the Judges to use the KHI, referring to the classical Islamic Jurisprudence when giving legal considerations and deciding cases of inheritance is not against the procedural law in Indonesia. Yet, this measure potentially creates the disparity of decisions in the Religious Courts since the fiqh differs in determining who the walad is: merely sons or include both sons and daughters. This has frustrated the objective of the KHI as the codification of Islamic Law in Indonesia which unites the differences of opinions in the fiqh and, thus, assures legal certainty in resolving the disputes. Hence, the government should enact the KHI as a Law in Indonesia in order to end the forum of choice for the Judges in basing their decisions so that the disparity of decisions in the Religious Court minimized and legal certainty assured for the justice seekers.Keywords: Islamic inheritance law, walad, fiqh, religious court's decision AbstrakArtikel ini didasarkan pada kenyataan bahwa masih ada perbedaan keputusan di antara Hakim Pengadilan Agama tentang ahli waris, terutama anak (walad), ketika menangani sengketa warisan. Ini karena ada ketentuan umum tentang makna walad yang terkandung dalam Kompilasi Hukum Islam Indonesia (KHI) di mana itu mencakup anak laki-laki dan perempuan. Selain itu, tidak ada kewajiban bagi Hakim Pengadilan Agama untuk menggunakan KHI sebagai dasar untuk pertimbangan hukum, yang memungkinkan beberapa Hakim Pengadilan Agama untuk menggunakan fiqh sebagai dasar hukum dalam memutuskan suatu kasus. Artikel ini bertujuan untuk menyelidiki dampak dari konsep umum walad (anak) dan langkah-langkah yang harus diambil Pemerintah untuk mengakomodasi bahan referensi hukum bagi para Hakim Pengadilan Agama, khususnya KHI dan fiqh. Artikel ini didasari oleh penelitian hukum normatif yang terutama meneliti keputusan Pengadilan Agama di Kalimantan Timur, khususnya Samarinda, Tenggarong dan Tanah Grogot. Temuan ini mengungkapkan bahwa karena tidak ada kewajiban bagi para Hakim untuk menggunakan KHI, merujuk pada Yurisprudensi Islam klasik ketika memberikan pertimbangan hukum dan memutuskan kasus-kasus warisan tidak bertentangan dengan hukum acara di Indonesia. Namun, langkah ini berpotensi menciptakan disparitas keputusan di Pengadilan Agama karena fiqh berbeda dalam menentukan siapa walad: hanya anak laki-laki atau termasuk anak laki-laki dan perempuan. Kondisi ini telah menggagalkan tujuan KHI sebagai kodifikasi Hukum Islam di Indonesia yang menyatukan perbedaan pendapat dalam fiqh dan, dengan demikian, memastikan kepastian hukum dalam menyelesaikan perselisihan. Oleh karena itu, pemerintah harus memberlakukan KHI sebagai UU di Indonesia untuk mengakhiri forum pilihan bagi para Hakim dalam mendasarkan keputusan mereka sehingga perbedaan keputusan di Pengadilan Agama diminimalkan dan kepastian hukum terjamin bagi para pencari keadilan.Kata Kunci: Hukum Kewarisan Islam, Konsep Walad, Fikih,  Putusan pengadilan agama